UPAYA MENINGKATKAN KEDISIPLINAN DALAM MATA PELAJARAN BROADCASTING MELALUI LAYANAN KONSELING INDIVIDUAL DENGAN PENDEKATAN BEHAVIORISTIK PADA SISWA KELAS XII BC 2 PROGRAM KEAHLIAN BROADCASTING SMKN 7 SURAKARTA TAHUN PELAJARAN 2015/2016 - Riptono, Riptono (UNIVERSITAS SLAMET RIYADI, 2016)
The research aims to improve discipline of students in broadcasting subject throughindividual counseling service with behaviorism approach at the XII Bc II Broadcasting programof SMKN 7 Surakarta in the academic year of 2015/2016. According to the result of pre-research,carried out by the researcher at the class on October 2015, there were some problems thereduring teaching learning process: there were three students, students OAN, RAP, and MA, whohad a problem because of less serious and not discipline during teaching and learning process,i.e. coming late to the classroom and not submitting the task in time. These caused guidance andcounseling teacher conducted particular guidance in solving the problems.The method of the research is a classroom action research. It has been conducted in twocycles about individual counseling service with behaviorism approach based on the problem ofthe student, i.e. not discipline during the teaching learning process.The research finding showed that the result of pre-cycle was 33.33 % (very low), cycle onewas 61.35% (moderate), and cycle two was 80% (high). After the counseling service wasconducted, there was a simultaneous improvement, however it needed to be monitored so that thestudents had discipline attitude by carrying out a practice to strengthen themselves and they wereaccustomed to obey and to manage themselves through the discipline attitude.Key Words: Counseling Service, Discipline